Intrinsic structural-ballistic interactions in composite energetic materials. Part II – Modeling - G. Sandri Tussiwand; F. Maggi; Bandera, A.; L. T. De Luca (ՀՀ ԳԱԱ հրատ.)
The structural properties of a propellant and the mechanical loads acting on it during deflagration can significantly alter its combustion behavior on a microscopic scale, leading to what can be considered as an “intrinsic” coupling mechanism. This can affect the performance of a solid rocket motor, and has been the subject of a study performed at the SPLab (Space Propulsion Laboratory) of Politecnico di Milano on AP-HTPB based composite propellant formulations. Part II of this study builds up from the results and experiments presented in Part I. Modeling activities were performed to understand and explain the coupling effect observed in the experiments and extrapolate them to motor’s conditions. A correlation between the average state of damage of the propellant and the burning rate is suggested.
Keywords: Քիմիա